Effect of esketamine nasal drops on pain in children after tonsillectomy using low temperature plasma ablation - Qian, Qiu; Liu, Hua Xian; Li, Yue Qing (Frontiers in Pediatrics, 2023)
Objective: To explore the effect of esketamine nasal drops on pain in children after tonsillectomy using low-temperature plasma ablation. Methods: 76 children who underwent tonsillectomy between May 2020 and July 2021, were randomly divided into two groups of 38 cases each. Patients in the control group were treated with conventional medication, while those in the study group were treated with esketamine nasal drops, along with the routine drug treatment. Pain levels of children in the two groups were compared within 1–3 days post-surgery, and the pseudomembrane formation and shedding-off time and recovery time were statistically analyzed. Results: The pain level of children in the study group was lower than that of the control group 1–3 days post-surgery. The pseudomembrane formation and shedding-off time and recovery time in the study group were shorter than in the control group (P < 0.05). There was no significant difference in the incidence of adverse reactions between the two groups, and there were no serious adverse reactions in the two groups (P > 0.05). Conclusion It is safe to use esketamine nasal drops in children after tonsillectomy using low temperature plasma ablation, and this is found to reduce pain and shorten the recovery time.